2014
DOI: 10.1016/j.ajpath.2014.07.003
|View full text |Cite
|
Sign up to set email alerts
|

B Cells Promote Tumor Immunity against B16F10 Melanoma

Abstract: B cells are known to be critical mediators of tumor immunity; however, the mechanisms through which they exert this function remain unclear. B-cell linker protein (BLNK) is an essential component of the B-cell antigen receptor signaling machinery and is required for B-cell development, as evidenced by BLNK-deficient (BLNK(-/-)) mice, in which the development and function of B cells are severely impaired. Herein, we evaluated the role of B cells in the development of tumor immunity against B16F10 melanoma using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…However, B cells are prominent players in autoimmunity and tissue rejection [ 30 ], implying their role in breaking tolerance, a key event in successful anti-tumor immunity [ 31 ]. Consistent with these findings, animal models of B cell deficiency show more aggressive growth of B16F10 melanoma, which can be ameliorated with adoptive B cell transfer [ 32 , 33 ]. In these models, B cells seem to promote T cell infiltration and cytokine production within the tumor.…”
Section: Discussionmentioning
confidence: 64%
“…However, B cells are prominent players in autoimmunity and tissue rejection [ 30 ], implying their role in breaking tolerance, a key event in successful anti-tumor immunity [ 31 ]. Consistent with these findings, animal models of B cell deficiency show more aggressive growth of B16F10 melanoma, which can be ameliorated with adoptive B cell transfer [ 32 , 33 ]. In these models, B cells seem to promote T cell infiltration and cytokine production within the tumor.…”
Section: Discussionmentioning
confidence: 64%
“…In a mouse model of B16 melanoma, DiLillo et al demonstrated that B-cell depletion was associated with faster tumor growth, increased lung metastasis, and decreased numbers of both CD4 + and CD8 + effector T cells (DiLillo, Yanaba, & Tedder, 2010). These observations were confirmed by Kobayashi et al in B-cell linker protein (BLNK)-deficient mice, another model of B-cell deficiency considered more relevant than μMT mice (Hayashi et al, 2000;Jumaa et al, 1999;Kobayashi et al, 2014;Minegishi et al, 1999;Pappu et al, 1999). In parallel, numerous clinical studies have demonstrated that a high density of B cells within the TME is associated with increased patient survival, for instance in CRC (Bindea et al, 2013).…”
Section: Role Of B Cellsmentioning
confidence: 55%
“…There are conflicting reports showing TIL-Bs have tumor-protective or tumor-promoting function. [145,146] TIL-Bs have been reported to be prevalent in human PC tissues. Gunderson et al [147] demonstrated human PC show increased expression of CD20 and immunoglobulin compared with normal pancreas.…”
Section: Adaptive Immune Cells In Pcmentioning
confidence: 99%